2020
DOI: 10.1186/s12913-020-4916-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving delivery of care in rural emergency departments: a qualitative pilot study mobilizing health professionals, decision-makers and citizens in Baie-Saint-Paul and the Magdalen Islands, Québec, Canada

Abstract: Background: Emergency departments (EDs) in rural and remote areas face challenges in delivering accessible, high quality and efficient services. The objective of this pilot study was to test the feasibility and relevance of the selected approach and to explore challenges and solutions to improve delivery of care in selected EDs. Methods: We conducted an exploratory multiple case study in two rural EDs in Québec, Canada. A survey filled out by the head nurse for each ED provided a descriptive statistical portra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Zulkifli et al (2019) said that nurses who work in remote health services try to provide actions according to patient needs even though with various limited facilities, this allows nurses who work to modify actions according to patient needs. Fleet et al (2020) said the challenge in providing emergency services at primary health centers is the limited facilities in the emergency unit.…”
Section: Limited Facilities and Infrastructure At The Puskesmasmentioning
confidence: 99%
“…Zulkifli et al (2019) said that nurses who work in remote health services try to provide actions according to patient needs even though with various limited facilities, this allows nurses who work to modify actions according to patient needs. Fleet et al (2020) said the challenge in providing emergency services at primary health centers is the limited facilities in the emergency unit.…”
Section: Limited Facilities and Infrastructure At The Puskesmasmentioning
confidence: 99%
“…Unfortunately, these isolated rural departments struggle with recruiting and retaining staff, and often have limited access to medical equipment and resources needed to provide comprehensive care in rural communities. 18 As a result, it had been suggested that rural populations would face a disproportionate amount of disadvantages with COVID-19, versus Canadians living in urban settings. 17 This was largely attributed to the fact that rural Canadians generally have worse health status, leading to an increase in Intensive Care Unit (ICU) admissions and increase mortality compared to urban populations.…”
Section: Emergency Departments In a Rural Contextmentioning
confidence: 99%
“…Children have unique healthcare needs due to physiological, development and psychological differences. ED teams in these general ED settings have identified gaps in accessing pediatric-specific training and resources, including opportunities for hands-on practice during courses or training experiences [2][3][4]. Moreover, they have expressed concerns in maintaining pediatric expertise and competencies particularly if they do not often treat children or certain pediatric conditions [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…ED teams in these general ED settings have identified gaps in accessing pediatric-specific training and resources, including opportunities for hands-on practice during courses or training experiences [2][3][4]. Moreover, they have expressed concerns in maintaining pediatric expertise and competencies particularly if they do not often treat children or certain pediatric conditions [2,4]. These concerns are well-founded; the gap in pediatric care between pediatric and general EDs has been associated with a disparity in health outcomes [5].…”
Section: Introductionmentioning
confidence: 99%